Quality of three Brachiaria varieties in Guayas area, Ecuador - Reyes-Pérez, J. J.; Méndez-Martínez, Y.; Luna-Murillo, R. A.; Verdecia, D. M.; Macias-Pettao, R.; Herrera, R. S. (Cuban Journal of Agricultural Science, 2019)
Using a random block design with factorial arrangement (3x3) with five replications, the quality of Brachiaria decumbens, Brachiaria brizantha and Brachiaria decumbens x Brachiaria ruziziensis cv. Mulato I at different regrowth ages (21, 42 and 63 days) were evaluated in Guayas area, Ecuador. The yields of total dry matter, biomass, leaves and stems were determined; as well as the plant height, length and width of leaves, the contents of DM, CP, NDF, ADF, ADL, cellulose (Cel), hemicellulose (Hcel), cellular content (CC), P, Ca, ash, OM, DMD, OMD, ME, LNE and relations leaf-stem, NDF-N and ADF-N. There was significant interaction (P <0.0001) between the varieties and the regrowth age for all the studied indicators. The highest DM and biomass yields were obtained in Mulato I at 63 days of regrowth (1.59 and 5.23 t/ha, respectively).The CP and CC decreased with the maturity of the plant and the best values were obtained in Mulato I at 21 days of regrowth (15.74 and 73.45 %, respectively), while the components of the cell wall increased with age and Brachiaria decumbens showed the highest values. There was variability in terms of the varieties in the studied indicators, with the best general performance for Mulato I. In this study the variability of the nutritional quality was showed by the interaction between the variety and the forage maturity, determined, among other aspects, by the decrease of digestibilities and the energy contribution, as well as increases of the relations NDF/N, ADF/N, it is important to highlight that the biomass production, total yields of leaves and stems, in addition to the morphological indicators height, number of leaves, length and width showed the best results in Mulato I at 63 days. Key words: quality, regrowth age, Brachiaria, digestibility, energy